Geothermal data from southeastern New Brunswick: Implications for potential geothermal energy projects and carbon sequestration in eastern Canada - Keighley, Dave; DeLuca, Joseph (Atlantic Geoscience, 2024)
To date, assessing the feasibility of Enhanced Geothermal Systems (EGS) in New Brunswick has been limited by the lack of information pertaining to geothermal gradients. Existing maps have incorporated less than a dozen datapoints, mostly from dedicated investigations in and adjacent to the central uplands that cross the province from southwest to northeast. To supplement this data, provincial records that report Bottom Hole Temperatures from exploration boreholes have been reviewed and coarsely filtered for dubious data. This process has contributed over 100 additional datapoints in the southeastern half of the province that have been converted to geothermal gradients to supplement previous maps. The updated geothermal map of southeastern New Brunswick indicates that geothermal gradients across the region average ~20.5 K/km, which is below the global average of 25 K/km. Locally, however, potential anomalies exist where geothermal gradients are well above the global average. These anomalies, pending further assessment, are associated with relatively shallow-depth salt intrusions. Elsewhere, the presence of high geothermal conductivity salt deposits has produced “salt chimneys” whereby overlying, near-surface rocks have steeper geothermal gradients than adjacent regions. Accordingly, whereas average values for regional geothermal gradients are not conducive to economic large-scale EGS using current technologies and may also lower the potential for economic sequestration of supercritical CO2, small-scale, lower temperature, shallow, geothermal systems may be feasible in localities associated with salt intrusions, particularly if further analysis supports a “salt-chimney” effect.